2020
DOI: 10.1111/clr.13662
|View full text |Cite
|
Sign up to set email alerts
|

Mechano‐adaptive Responses of Alveolar Bone to Implant Hyper‐loading in a pre‐clinical in vivo model

Abstract: Objectives: Oral implants transmit biting forces to peri-implant bone. In turn, those forces subject peri-implant bone to mechanical stresses and strains. Here, our objective was to understand how peri-implant bone responded to conditions of normal versus hyper-loading in a mouse model. Material and Methods: Sixty-six mice were randomly assigned to 2 groups; both groups underwent bilateral maxillary first molar extraction followed by complete healing. Titanium alloy implants were placed in healed sites and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…This makes sense from a biomechanical point of view, given the near-perpendicular position with respect to the floor of the tibia of the rabbit and the perpendicular arrangement of the implants with respect to the major axis of the tibia. These findings are consistent with the outcomes of the histological analyses by Tian et al in a recent study on the mechanoadaptive response of the alveolar bone to implant hyperloading during an experimental study in rats [64]. This concept is the main hypothesis of this study, and it gives rise to "the bone buttress theory" that was previously proposed by the authors of a previously published clinical study [3]; the osseointegration of immediately loaded dental implants can be based on the apposition of a load-oriented bone, like the flying buttresses of a Gothic church, rather than on a poorly oriented woven bone typical of osseointegration following conventional loading.…”
Section: Discussionsupporting
confidence: 92%
“…This makes sense from a biomechanical point of view, given the near-perpendicular position with respect to the floor of the tibia of the rabbit and the perpendicular arrangement of the implants with respect to the major axis of the tibia. These findings are consistent with the outcomes of the histological analyses by Tian et al in a recent study on the mechanoadaptive response of the alveolar bone to implant hyperloading during an experimental study in rats [64]. This concept is the main hypothesis of this study, and it gives rise to "the bone buttress theory" that was previously proposed by the authors of a previously published clinical study [3]; the osseointegration of immediately loaded dental implants can be based on the apposition of a load-oriented bone, like the flying buttresses of a Gothic church, rather than on a poorly oriented woven bone typical of osseointegration following conventional loading.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, our data align with multiple clinical reports in the literature, showing that alveolar bone has a remarkable degree of adaptability to changing mechanical conditions (Tian et al, 2020;Watson et al, 2018;Yeh & Popowics, 2011). In addition, other investigators have also reported 10%-12% higher bone-implant contact for loaded versus submerged oral implants (Tumedei et al, 2020), and our data provide a plausible explanation for this observation.…”
Section: The Relevance Of Rodent Data To Patient Outcomessupporting
confidence: 91%
“…First, we compared bone remodeling activity around teeth to remodeling activity around implants that were free from occlusal contact (Tian et al, 2020). Results from this study demonstrated that the remodeling activity stimulated by implant placement returns to baseline levels within 21 days (Tian et al, 2020). Since implants were not subjected to masticatory loads, we could reliably conclude that the remodeling activity within this 3‐week period was solely due to implant placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] The Mechanostat theory, first proposed by Frost in 1987 describes a regulatory mechanism within bone that deals with strain magnitude and invokes bone formation and resorption as the primary "effector mechanisms" by which bone alters its structure and properties in response to mechanical usage. [23] Frost's theory suggests that bone can act like a mechanostat, in that it brings about a biomechanical adaptation, corresponding to the external loading condition. The theory proposed four microstrain zones, which correlated to a mechanical adaptation: (a) disuse atrophy; (b) steady state; (c) physiological overload; and (d) pathological loading.…”
Section: Discussionmentioning
confidence: 99%